2003
DOI: 10.1007/s005400300023
|View full text |Cite
|
Sign up to set email alerts
|

MAC reduction after intrathecal coadministration of GABA A agonist and glutamate antagonist in rats

Abstract: Intrathecal coadministration of a GABA(A) agonist and an NMDA or AMPA antagonist, which has been reported to produce a synergistic antinociceptive effect, did not induce a synergistic reduction in the MAC. The antinociceptive effect may not be the predominant factor in the reduction of the MAC induced by these drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…Thus, we conclude that spinal AMPA receptors may be important targets for the analgesic effects of emulsified enflurane, isoflurane and sevoflurane. This is in accord with the observations of Sumikura and Arendt-Nielsen, 27 who found that i.t. administration YM872 (an AMPA receptor antagonist) produced a maximal decrease of 31.4% in sevoflurane MAC.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Thus, we conclude that spinal AMPA receptors may be important targets for the analgesic effects of emulsified enflurane, isoflurane and sevoflurane. This is in accord with the observations of Sumikura and Arendt-Nielsen, 27 who found that i.t. administration YM872 (an AMPA receptor antagonist) produced a maximal decrease of 31.4% in sevoflurane MAC.…”
Section: Discussionsupporting
confidence: 93%
“…Inhalation anaesthetics have been reported to attenuate excitatory neurotransmission in the CNS, particularly at glutamate synapses 3–5 . Intrathecal administration of a glutamate receptor antagonist has also been reported to produce an antinociceptive effect and reduce the MAC 27,28 . The excitatory effect of glutamate on nociception is mediated by at least two distinct classes of receptors, AMPA receptors and N ‐methyl‐ d ‐aspartate(NMDA) receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As predicted by our hypotheses, we conclude that spinal AMPA receptors may be important targets for the analgesic effects of emulsified enflurane, isoflurane and sevoflurane. This is in accord with the observation of Sumikura and Arendt‐Nielsen [33] who found that intrathecal administration YM872 (AMPA receptor antagonist) produced a maximal decrease of 31.4% in sevoflurane MAC. Similarly, McFarlane et al .…”
Section: Discussionsupporting
confidence: 92%
“…infusion of MK801 (NMDA receptor antagonist) produced a maximal decrease of 65% in isofl urane MAC. Similarly, Sumikura and Arendt-Nielsen [18] found that i.t. infusion of AP5 produced a maximal decrease of 30% in sevofl urane MAC.…”
Section: Discussionmentioning
confidence: 99%